Dent's disease in a child with nephrolithiasis [Nefrolityazis tanısıyla başvuran bir olguda dent hastalıǧı] - ALPAY, HARİKA; GÖKCE, İBRAHİM; YILDIZ, NURDAN (Kare Publishing, 2013)
[No abstract available]